The impacts of the minimum wage on the labor market, poverty and fiscal budget in Brazil - Miguel Nathan Foguel; Lauro R. A. Ramos; Francisco Galr\~ao Carneiro (Institute for Applied Economic Research (ipea), 2015)
This paper aims at contributing to the debate regarding the role of the minimum wage in Brazil. This is carried out by assessing its potential effects on the labor market outcomes, as well in terms of poverty alleviation and fiscal impact. First, a succinct description of the institutional framework, the evolution of its real value over time, and a characterization of the profile of minimum wage earners are presented. Next, after a brief survey of theoretical views and empirical results found in the literature, the estimations, as well their implications in terms of minimum wage policies, are presented and discussed.
Keywords: 330